Development, cytotoxicity and eye irritation profile of a new sunscreen formulation based on benzophenone-3-poly(-caprolactone) nanocapsules - Barbosa, Thallysson Carvalho (2019)
The objective of this work was to characterize the toxicological profile of a newly developed sunscreen formulation based on polymeric nanocapsules (NCs) loading benzophenone-3 (BZP3). NCs composed of poly(ε-caprolactone) carrot oil and Pluronic® F68 were produced by emulsification-diffusion method. Their mean particle size (Z-Ave) ranged from 280 to 420 nm, polydispersity index (PDI) was below 0.37, while zeta potential (ZP) reached about |+11 mV|. No cytotoxic effects were observed in L929 fibroblast cell line for the blank (i.e., non-loaded) NCs and BZP3-loaded NCs (BZP3-NCs). The semi-solid sunscreen formulation was stable over time (centrifugation testing) and exhibited non-Newtonian pseudoplastic behavior, which is typical of products for topical application onto the skin. The sun protection factor (SPF) value reached 8.84, when incorporating BZP3-NCs (SPF of 8.64) into the semi-solid formulation. A synergistic effect was also observed when combining the formulation ingredients of nanocapsules, i.e., SPF of carrot oil was 6.82, blank NCs was 6.84, and BZP3-loaded NCs was 8.64. From the hen’s egg-chorioallantoic membrane test (HET-CAM) test, the non-irritation profile of the developed formulations could also be confirmed. The obtained results show a promising use of poly(ε-caprolactone) nanocapsules to be loaded with lipophilic sunscreens as benzophenone-3.